The context of emergency contraception use among young unmarried women in Accra, Ghana: a qualitative study - Slawa Rokicki; Sonja Merten (BMC, 2018)
Abstract Background Over the past decade, awareness and use of emergency contraceptive pills (ECPs) among young women has rapidly increased in Ghana; however, the rate of unintended pregnancy among this group remains high. We conducted a qualitative study to better understand the context and patterns of ECP use among young unmarried women in Ghana. Methods We conducted in-depth interviews with unmarried sexually active women aged 18-24 in Accra, Ghana to explore their perceptions, experiences, and opinions regarding sexual relationships and contraceptive methods, and to examine the factors that influence choice of ECPs. A total of 32 young women participated in the study. Results Most participants had used ECPs at least once. Participants described being unable to plan for sexual encounters, and as a result preferred ECPs as a convenient post-coital method. Despite being widely and repeatedly used, women feared the disruptive effects of ECPs on the menstrual cycle and were concerned about long-term side-effects. ECPs were sometimes used as a back-up in cases of perceived failure of traditional methods like withdrawal. Misinformation about which drugs were ECPs, correct dosage, and safe usage were prevalent, and sometimes spread by pharmacists. Myths about pregnancy prevention techniques such as urinating or washing after sex were commonly believed, even among women who regularly used ECPs, and coincided with a misunderstanding about how hormonal contraception works. Conclusions ECPs appear to be a popular contraceptive choice among young urban women in Ghana, yet misinformation about their correct usage and safety is widespread. While more research on ECP use among young people is needed, these initial results point to the need to incorporate information about ECPs into adolescent comprehensive sexuality education and youth-friendly services and programmes.